The main phenomena of space crews’ communication as a rationale for the modification of mission control communicative style - Supolkina, Natalia; Shved, Dmitry; Yusupova, Anna; Gushin, Vadim (Frontiers in Psychology, 2023)
The article describes the phenomena of communication between space crews and the Mission Control Center studied within the framework of the “Content” space experiment. The main objective was discussion of the relationship of the psychological state of cosmonauts, studied on the basis of crew communication content analysis, with their need for social psychological support. The ideas about social psychological support in the context of crew - Mission Control Center (MCC) communication are outlined. Relevant practical recommendations are presented for modifying the communication style of the MCC personnel to psychologically support the crews. The principles and recommendations for effective communication will both provide continuous psychological support to the space crews in orbit and reduce the likelihood of emotional burnout among MCC personnel.